Development and Factor Structure of the Helping Professional Wellness Discrepancy Scale. (3rd April 2018) - Blount, Ashley J.; Lambie, Glenn W.
ABSTRACT: The authors present the development of the Helping Professional Wellness Discrepancy Scale (HPWDS). The purpose of this article is threefold: (a) present a rationale for the HPWDS; (b) review statistical analyses procedures used to develop the HPWDS; and (c) offer implications for counselors, other helping professionals, and future research.